Effect of Self-determination Theory-based Discharge Program on Lifestyle and Readmission of Patients with Heart Failure: A Clinical Trial - Tahere Sarboozi Hosein َAbadi; Mohammad Namazi Nia; Seyed Reza Mazlom (Mashhad University of Medical Sciences, 2020)
Background: Lifestyle and behaviors of human beings are major factors in cardiovascular diseases. Therefore, a discharge program based on Self-determination Theory could improve the lifestyle of the patients. Aim: This study aimed to determine the effect of this program on the lifestyle and readmission of patients with heart failure. Method: This clinical trial was performed on 60 patients with heart attack in a city in north-east of Iran, during 2018-19. The participants were selected by convenience sampling method and divided randomly into intervention and control groups. Subsequently, the intervention group was subjected to a 12-week SDT-based discharge program. However, the control group received the routine program. The data were collected using a demographic characteristics form, the Health-Promoting Lifestyle Profile II questionnaire, and the readmission questionnaire. Moreover, the data were analyzed in SPSS software (version 20) using the Chi-square, independent t-test, paired t-test, and Wilcoxon. Results: In total, 20.0% and 46.7% of the subjects in the intervention and control groups were re-hospitalized, respectively. The Chi-square showed a significant difference in this regard (P=0.028).The results also showed a significant increase in the lifestyle score of the patients at post-test stage, in the intervention group (164.6±16.9), compared to the control group (119.1±17.2) (P<0.001). Furthermore, the mean score of various lifestyle subscales significantly increased in the intervention group, compared to the control group, three months after discharge (P<0.01). Implications for Practice: The design and implementation of a SDT-based discharge program could be included in the nursing care program as an effective method to create and maintain health-promoting behaviors.